A survey of core replacements in indole-based HIV-1 attachment inhibitors. Issue 11 (1st June 2019) - Wang, Tao; Wallace, Owen B.; Zhang, Zhongxing; Fang, Haiquan; Yang, Zhong; Robinson, Brett A.; Spicer, Timothy P.; Gong, Yi-Fei; Blair, Wade S.; Shi, Pei-Yong; Lin, Pin-Fang; Deshpande, Milind; et al.
Graphical abstract: Abstract: Indole- and azaindole-based glyoxylyl amide derivatives have been described as HIV-1 attachment inhibitors (AIs) that act by blocking the interaction between the viral gp120 coat protein and the human host cell CD4 receptor. As part of an effort to more deeply understand the role of the indole/azaindole heterocycle in the expression of antiviral activity, a survey of potential replacements was conducted using parallel synthesis methodology. The design and optimization was guided by a simple 2-dimensional overlay based on an overall planar topography between the indole/azaindole and C-7 substituents that had been deduced from structure-activity studies leading to the discovery of temsavir (3 ). 2-Substituted naphthalene- and quinoline-derived chemotypes emerged as the most interesting prototypes, with C-5 and C-6 substituents enhancing antiviral potency. Despite the fact that neither of these chemotypes incorporated a H-bond donor that has been shown to engage the side chain carboxylate of Asp113 in gp120, the antiviral potency of several analogues met or exceeded that of3, demonstrating that engaging Asp113 is not a prerequisite for potent antiviral activity.